Association Between Substance Use and Gun-Related Behaviors. (13th January 2016) - Chen, Danhong; Wu, Li-Tzy
Abstract : Gun-related violence is a public health concern. This study synthesizes findings on associations between substance use and gun-related behaviors. Searches through PubMed, Embase, and PsycINFO located 66 studies published in English between 1992 and 2014. Most studies found a significant bivariate association between substance use and increased odds of gun-related behaviors. However, their association after adjustment was mixed, which could be attributed to a number of factors such as variations in definitions of substance use and gun activity, study design, sample demographics, and the specific covariates considered. Fewer studies identified a significant association between substance use and gun access/possession than other gun activities. The significant association between nonsubstance covariates (e.g., demographic covariates and other behavioral risk factors) and gun-related behaviors might have moderated the association between substance use and gun activities. Particularly, the strength of association between substance use and gun activities tended to reduce appreciably or to become nonsignificant after adjustment for mental disorders. Some studies indicated a positive association between the frequency of substance use and the odds of engaging in gun-related behaviors. Overall, the results suggest a need to consider substance use in research and prevention programs for gun-related violence.